Investigating the awareness of onsite mechanization in malaysian construction industry - Waris, M. (Elsevier Ltd, 2014)
The Malaysian construction industry is vital for the country economy and always played a key role towards the development of national infrastructure. The ever-increasing market competitiveness and the widespread adoption of Industrialized Building System (IBS) by the local contractors derive the industry to improve the existing processes for achieving higher levels of quality and products. This transition from traditional methods of construction give a momentum to the deployment of onsite mechanized equipments. The utilization of mechanized equipments increases construction productivity and as well as reduces the dependency on foreign labour. However, a large amount of construction company's capital is also invested in procuring these equipments. In addition to this, varieties of construction equipments are also required for carrying out these operations. Therefore, the aim of this paper is to investigate the current awareness and application of onsite mechanization in Malaysian construction industry. A questionnaire survey was conducted among a classified group of Construction Industry Development Board of Malaysia (CIDB) G7 Class 'A' contractors. The results of the survey show that there is a good understanding of Malaysian contractors towards mechanization. It is also revealed that the adoption of IBS have a direct correlation with the usage of onsite machineries and equipments. Results further indicate that excavation, earthworks, pilling works and structural works have high utilization of mechanized construction equipments. The study will help to find out the existing level of mechanization practices in Malaysian construction industry. Â© 2014 The Authors. Published by Elsevier Ltd.